Visions of Community Health and the Social Good in Kenya: Turning Community Health Workers into Entrepreneurs - Edwin Ambani Ameso; Ruth Jane Prince (Development and Change, 2025)
In East Africa, social enterprises that fuse development work with entrepreneurial activities and a language of `innovation' are becoming prominent. Critical of the NGO/donor model, which they hold as unsustainable, such organizations are funded by corporate investment and philanthropic capital but aim for self-reliance through enlisting local actors to market social services, while providing loans, digital infrastructures and training in entrepreneurship. Based on ethnographic fieldwork in Kenya, this article examines the ethos, ambitions and practices of one such enterprise operating across Africa — Healthy Entrepreneurs. This not-for-profit organization seeks to enable community health workers to become `health entrepreneurs' by training them in business management and offering them a loan and mobile phone from which they order health commodities online and sell them to rural communities. Focusing on the perspectives, motivations and experiences of local managers and the entrepreneurs themselves, the article explores relations between entrepreneurism, community health work, sustainability and the `social good', and the frictions surrounding them. The model of turning community health workers into entrepreneurs, which fosters competition while placing the burden of success onto the individual, shifts the ethos of community health work towards a focus on business. However, the moral economies in which community health entrepreneurs are embedded complicates this picture.
Keywords: 300